2008
DOI: 10.1016/j.exphem.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble urokinase plasminogen activator receptor (suPAR) is associated with thrombosis and inhibition of plasmin generation in paroxysmal nocturnal hemoglobinuria (PNH) patients

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired genetic disorder of the bone marrow that produces intravascular hemolysis, proclivity to venous thrombosis, and hematopoietic failure. Mutation in the PIG-A gene of a hematopoietic stem cell abrogates synthesis of glycosylphosphoinositol (GPI) anchors and expression of all GPI-anchored proteins on the surface of progeny erythrocytes, leukocytes, and platelets. Urokinase plasminogen activator receptor (uPAR), a GPI-linked protein expressed on neutrophils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…29 Accordingly, uPAR is absent from the cell surface of leukocytes affected by the PNH driver mutations; these abnormal cells respond by secreting a soluble intact receptor, thus sustaining chronically elevated levels of suPAR in the plasma of patients with PNH. [29][30][31][32] Despite these abnormally high levels of suPAR in the plasma of patients with PNH, to the best of our knowledge, FSGS is not one of the prevalent renal lesions observed in these patients. 33 Renal dysfunction does occur in patients with PNH, but most of these clinical features can be alleviated by eculizumab treatment, highlighting chronic complement-mediated hemolysis as the driver of renal pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Accordingly, uPAR is absent from the cell surface of leukocytes affected by the PNH driver mutations; these abnormal cells respond by secreting a soluble intact receptor, thus sustaining chronically elevated levels of suPAR in the plasma of patients with PNH. [29][30][31][32] Despite these abnormally high levels of suPAR in the plasma of patients with PNH, to the best of our knowledge, FSGS is not one of the prevalent renal lesions observed in these patients. 33 Renal dysfunction does occur in patients with PNH, but most of these clinical features can be alleviated by eculizumab treatment, highlighting chronic complement-mediated hemolysis as the driver of renal pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that factors correlating with markedly elevated levels of soluble uPAR included the absolute number and percent of GPI-negative neutrophils, and absolute neutrophil count. 20 Other investigators highlighted enhanced platelet activation and elevated levels of circulating procoagulant microparticles derived from platelets and/or endothelial cells. [12][13][14][15] It has also been suggested that PNH platelets, which likely correlate with the size of PNH clone, may trigger a prothombotic cascade due to lack of certain GPI-deficient proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating thrombophilia in PNH implicated several possible mechanisms; however, none of the pathways described to date provide sufficient explanation for the extraordinarily high risk of thrombosis in these patients. [11][12][13][14][15][16][17][18][19][20] For example, abnormalities of the fibrinolytic cascade mediated through deficiency of the GPIlinked uPAR normally present on platelets and leukocytes have been described. Competitive binding of pro-uPA by an excess of soluble uPAR could contribute to a deficiency of fibrinolytic activity as could the loss of active uPA normally localized to thrombi by binding to uPAR on cells within a clot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibody recognizes the human β3 integrin GPINCT sequence, which is absent in mouse β3 integrin 8 . Third, paroxysmal nocturnal haemoglobinuria (PNH) is a rare acquired bone marrow disorder in which suPAR overproduc tion and/or accumulation is linked to the dysfunction of glycosylphosphatidylinositol anchoring, leading to very high levels of circulating suPAR [9][10][11] . As the disease occurs in haematopoietic stem cells (at least in early myeloid progenitor cells), PNH might represent the human counterpart of experimental conditions discussed in the commentary (that is, the effects of high levels of circulating suPAR coming from haematopoietic sources).…”
mentioning
confidence: 99%